Trifolirhizin: A Phytochemical with Multiple Pharmacological Properties - Varun Jaiswal; Hae-Jeung Lee (Molecules)
Trifolirhizin is an important flavonoid glycoside reported from the roots of medicinal plants such as Astragalus membranaceus, Sophora tonkinensis, Ononis vaginalis, Euchresta formosana, Sophora Subprostrate, Ononis spinose, and Sophora flavescens. It is considered one of the important constituents responsible for the various medicinal properties of these medicinal plants. Studies have revealed the multiple pharmacological properties of trifolirhizin: anti-inflammatory, antioxidant, antibacterial, anti-ulcerative colitis, antiasthma, hepatoprotective, osteogenic, skin-whitening, wound-healing, and anticancer (against various types of cancers). Mechanistic studies of trifolirhizin showed that it could act on important target genes and pathways such as the NF-κB-MAPK, EGFR-MAPK, AMPK/mTOR, and PI3K/Akt signaling pathways. These pathways are also implicated in various other diseases, suggesting the potential of trifolirhizin in therapeutic applications. Initial pharmacokinetic studies support the therapeutic candidature of trifolirhizin and provide the initial track that may be pursued for its development. Still, a compilation of pharmacological activities and target pathways of trifolirhizin is missing in the literature. This review uniquely compiles the pharmacological properties and mechanistic insights of trifolirhizin, addressing critical gaps in its therapeutic development and proposing strategies for future research.